PENGARUH FASILITAS DAN INTELEKTUALITAS TERHADAP KINERJA KARYAWAN PT. BANK PERKREDITAN RAKYAT PEMBANGUNAN KERINCI (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2023)
This study aims to determine the effect of facilities and intellectuality on employee performance at PT. Bank Perkreditan Rakyat Pembangunan Kerinci. The population in this study amounted to 40 people, namely all employees of PT. People's Credit Bank for Kerinci Development. While the sample size of 35 respondents with the sampling technique Probability Sampling is a sampling method in which every member of the population has the same opportunity to be selected as a sample. The data analysis technique used in this research is Multiple Linear Regression Analysis. The study results stated a significant influence between facilities and intellect on the performance of employees of PT. BPR Pembangunan Kerinci partially or simultaneously has a significant influence.